2017
DOI: 10.1016/j.crad.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Improving national standards of child protection skeletal surveys: the value of College guidance

Abstract: There has been an improvement in the content of skeletal surveys performed in England, which in part may be due to the publication of the national joint Royal College guidance; however, there remain areas for continued development in order to improve practice further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Since the publication of the RCR‐RCPCH guidelines, a study by Patel et al, looking at 100 skeletal surveys, found that 51% of studies contained all recommended views and each view had an average quality score 97%. A retrospective evaluation by Weldon and Price, which analysed 121 NAI skeletal survey examinations, found the implementation of imaging checklists improved skeletal survey quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the publication of the RCR‐RCPCH guidelines, a study by Patel et al, looking at 100 skeletal surveys, found that 51% of studies contained all recommended views and each view had an average quality score 97%. A retrospective evaluation by Weldon and Price, which analysed 121 NAI skeletal survey examinations, found the implementation of imaging checklists improved skeletal survey quality.…”
Section: Resultsmentioning
confidence: 99%
“…27 The content and quality of the skeletal survey should be consistent between institutions, to improve the detection and ensuring accurate reporting of the images. 6…”
Section: Conventional Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…This follow-up period presents a temporal medicolegal challenge for the police and social services, because the child needs to be in a safe place and potential perpetrators need to be identified quickly. Together with evidence that hospitals, social workers, parents, and children adhere poorly to the schedule of follow-up radiographs,24, 25 we argue that the use of CT in the acute setting in which radiographs are negative or unequivocal will probably identify otherwise undetected rib fractures, providing immediate diagnostic information, which is preferable to waiting for follow-up radiographs. Because all infants suspected of physical abuse will undergo a head CT to look for intracranial injury as per national guidelines, 1 we argue that the addition of a subsievert chest CT during the same attendance would be pragmatic.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, eradicating this phenomenon can significantly enhance healthcare outcomes. To adequately diagnose affected children, taking a full history and full examination of the child is essential when formulating a proper decision (5). It has been demonstrated that radiological skeletal assessment is a critical tool for assessing and adequately diagnosing the physical abuse of children.…”
Section: Introductionmentioning
confidence: 99%